Odpowiedzi

2013-02-17T14:35:37+01:00

a)\frac{1}{3}x-2=x+2|*3\\ x-6 = 3x +6\\ x-3x = 12\\ -2x=12|:(-2)\\ x=-6\\

 

b) 1 - \frac{6}{7}x = \frac{4}{7}|*7\\ 7 - 6x = 4 \\ -6x = 4 - 7 \\ -6x= -3|:(-6)\\ x= \frac{3}{6}\\ x= \frac{1}{2}

 

c) 6 (\frac{1}{4}x - 2 ) = 18\\ \frac{3}{2}x -12 = 18 |*2 \\ 3x - 24 = 36 \\ 3x = 36+24\\ 3x = 60|:3\\ x= 20

 

d) \frac{x}{6}- \frac{1}{6}= 1|*6\\ x-1 = 6 \\ x= 6+1\\ x= 7

 

e) -2(2x-1) = \frac{x}{3}\\ -4x +2 = \frac{x}{3}|*3\\ -12x +6 = x \\ -12x - x =- 6 \\ -13x = -6 |: (-13)\\ x =\frac{6}{13}

 

f) \frac{2}{5}(3-x)=-2\\ \frac{6}{5}-\frac{2}{5}x = -2|*5\\ 6-2x= -10 \\ -2x = -10 -6 \\ -2x = -16 |:(-2)\\ x= 8

 

g)\frac{3}{4}(2 - 3x) = -6 \\ \frac{6}{4}-\frac{9}{4}x = -6|*4\\ 6 - 9x = -24 \\ -9x = - 24 - 6 \\ -9x = -30:(-9) \\ x= \frac{30}{9}\\ x= 3\frac{1}{3}

 

h) \frac{1}{5}(x-3) = 9 - x \\ \frac{1}{5}x - \frac{3}{5}= 9 - x |*5\\ x - 3 = 45 - 5x\\ 6x = 45 +3\\ 6x = 48 |:6\\ x= 8

 

i) \frac{6}{10}+\frac{x}{2}= x+1\\ \frac{6}{10}+\frac{5x}{10}= x+1|*10\\ 6 +5x = 10x +10\\ 5x -10x = 10 -6 \\ -5x = 4|:(-5)\\ x= -\frac{4}{5}

74 4 74